Rock Slope Stability Assessment Using Photogrammetric Mapping And Limit Equilibrium Method - Tung, Wen Yan (Universiti Sains Malaysia, 2018)
Rock slope excavation is unavoidable for the infrastructure development in our country such as expressway and water channel. Hence, a proper rock slope characterization and support design has to be carried out to ensure the stability of the rock slope, preventing hazardous events. Measuring discontinuity orientation in the rock slope by traditional scanline survey is time consuming and challenging due to the accessibility issue. Structure from motion (SfM) photogrammetry using UAV permits a fast and inexpensive way to do survey mapping for geotechnical characterization of rock slopecompared to terrestrial laser scanner (TLS). Images that are captured and going through bundle adjustment with ground control points (GCPs) render within centimetre accuracy of dense point cloud, 3D model, orthophoto and digital surface model (DSM). A case study was conducted at the rock slope of Projek Lencongan Banjir Barat Timah Tasoh, Perlis. Dense point cloud is imported into CloudCompare to extract the geological planes. The discontinuities extracted are reliable and accurate as they are within 7° of the data measured manually. By using discontinuity data, the kinematic analysis shows that the rock slope has 15.40% of risk in planar sliding, 7.16% in wedge sliding and 1.33% in flexural toppling. Rock slope stability is analysed by deterministic Limit Equilibrium Method (LEM) in 3D and 2D and probabilistic LEM in 2D, utilising the 3D rock slope model geometry and orientation discontinuity extracted as well as the parameters obtained from the database. By comparing deterministic method, FoS obtained from 3D analysis (0.908) is higher than 2D analysis (0.591). On the other hand, by comparing probabilistic and deterministic method in 2D analysis, probabilistic method renders lower FoS (0.336) than deterministic method (0.591). Probabilistic method is more conservative as it considers the heterogeneity characteristic of the rock mass.